2021
DOI: 10.1128/jvi.02335-20
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Hemagglutinating Encephalomyelitis Virus Infection In Vivo and Ex Vivo

Abstract: Porcine hemagglutinating encephalomyelitis virus (PHEV) is a Betacoronavirus that causes vomiting and wasting disease and/or encephalomyelitis in suckling pigs. This study characterized PHEV infection, pathogenesis, and immune response in caesarean-derived, colostrum-deprived (CDCD) neonatal pigs. Infected animals developed mild respiratory, enteric, and neurological clinical signs between 2 to 13 days post oronasal inoculation (dpi). PHEV did not produce viremia, but virus shedding was detected in nasal secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In a previous study ( 6 ), we reported the detection of significant PHEV RNA levels in tracheal tissues collected from pigs experimentally inoculated with PHEV and necropsied on day postinfection (dpi) 5. As a continuation, in the present study, we performed transcriptome analysis (45 target genes) of these tracheal tissues in comparison to their corresponding mock-inoculated pigs as the negative control.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study ( 6 ), we reported the detection of significant PHEV RNA levels in tracheal tissues collected from pigs experimentally inoculated with PHEV and necropsied on day postinfection (dpi) 5. As a continuation, in the present study, we performed transcriptome analysis (45 target genes) of these tracheal tissues in comparison to their corresponding mock-inoculated pigs as the negative control.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the virus was first isolated in 1970 from the nasal cavity of apparently healthy pigs during a routine diagnostic survey ( 8 ), and viral antigens were detected inside the cytoplasm of the epithelial cells lining nasal mucosa, bronchi, and bronchioles ( 12 ). Our group further demonstrated that, under in vivo and ex vivo experimental conditions, PHEV (67N strain) replicates in the upper respiratory tract epithelium and tonsil of cesarean-derived, colostrum-deprived (CDCD) neonatal pigs ( 6 ). Therefore, as for many other pathogens with respiratory tropism, respiratory epithelial cells could play a vital role in initiating and shaping the crucial defensive immunological processes during PHEV infections.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations